Forward and multiple directions single leg hop results in soccer player: evaluation of pre-season - Akyüz, Öznur (Progress in Nutrition, 2022)
Study Objectives: This study aimed to determine the Single Leg Hop Tests (SLHT) and Limb Symmetry Index (LSI) and to examine possible injury risks in football players with lower extremity strength differences. Methods: The study group of the research consisted of 21 male football players between the ages of 18-35 who had at least 10 years of active football training and were regularly trained. Participants had 3 different SLHT on dominant (DS) and non-dominant (NDS) sides; Single Leg Hop for Distance (SL), Crossover Hop for Distance (CHD), and Medial Side Triple Hop for Distance (MSTH) tests were applied. Paired sample t, One Way ANOVA, Tukey, and Pearson tests were used in the statistical analysis of the research. Results: In the SL test, it was determined that the left side had a higher jump distance than the right side (p<0.05), but the CHD and MSTH tests did not reveal any significant differences (p>0.05). In different SLHT, LSI was detected at the rates of 97.22% in the SL test, 99.71% in the CHD test, and 99.19% in the MSTH test. Conclusion: When the results of our research were evaluated, it was determined that the detected LSI ratios reflected very low levels of asymmetries and that the football players forming the subject group had balanced strength developments between the DS and NDS limbs. In this context, it was evaluated that the risk of injury in the pre-season measurements of the football players was low.